"So we tell them": articulating strong Black masculinities in an urban Indigenous community. (September 2019) - Mukandi, Bryan; Singh, David; Brady, Karla; Willis, Jon; Sinha, Tanya; Askew, Deborah; Bond, Chelsea
There is a growing literature on Indigenous masculinities written by scholars in North America, Hawai'i and New Zealand which draws on a variety of approaches. While there are signs of scholarly interest in Aboriginal and Torres Strait Islander masculinities in Australia, this has yet to translate into a distinct body of work. This article is a potential opening onto such a future corpus, foregrounding and privileging how Aboriginal and Torres Strait Islander men understand themselves. Interviews with 13 men, ranging in age from young teenagers through to Elders—among whom were Traditional Owners, school pupils, university students, community workers, health professionals and retirees—yielded a conception of Indigenous masculinities not concerned with recovering a lost masculinity. Rather, what was presented to us is a distinct conception of Indigenous masculinities rooted in place; a relationality motivated by an intergenerational sense of responsibility; a nuanced idea of "acting hard."